The role of the PTEN/mTOR axis in clinical response of rectal cancer patients - ORUN, OYA; MEGA TİBER, PINAR (My University, 2022)
© 2022, The Author(s), under exclusive licence to Springer Nature B.V.Background: Preoperative chemoradiotherapy has long been accepted as a method to improve survival and lifetime quality of rectal cancer patients. However, physiologic effects of these therapies largely depend on the resistance of cells to the radiation, type of chemotherapeutic agents and individual responses. As one of the signaling cascades involved in chemo- or radiation- resistance, the present study focused on several proteins involved in pTEN/Akt/mTOR pathway to explore their prognostic significance. Materials and methods: Samples from advanced stage rectal cancer patients were analyzed to detect expression levels of pTEN/Akt/mTOR pathway related proteins pTEN, mLST8, REDD1, BNIP3, SAG and NOXA, together with p53, by RT-qPCR. Kaplan–Meier analysis was used to assess expression-survival relation and correlations among all proteins and clinicopathological features were statistically analyzed. Results.: Except p53, none of the proteins showed prognostic significance. High p53 expression presented clear impact on overall survival and disease free survival. It was also significantly related to pathologic complete response. p53 showed high correlation to local recurrence as well. On the other hand, strong correlation was observed with PTEN expression and tumor response, but not with survival. High associations were also observed between mLST8/REDD1, PTEN and NOXA, confirming their role in the same cascade. Conclusion: The contentious role of p53 as a prognostic biomarker in colorectal cancer was further affirmed, while PTEN and REDD1 could be suggested as potential candidates. Additionally, NOXA emerges as a conjunctive element for different signaling pathways.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Natural Sciences; Yaşam Bilimleri (LIFE); Moleküler Biyoloji ve Genetik; GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; GENETICS & HEREDITY; Moleküler Biyoloji; Genetik; Molecular Biology; Genetics; Rectum cancer; PTEN; p53; mTOR; mLST8; REDD1; NOXA; E3 UBIQUITIN LIGASE; PTEN FUNCTION; PROGNOSTIC ROLE; MTOR INHIBITOR; POOR-PROGNOSIS; EXPRESSION; GENE; MUTATION; BNIP3; Rectum cancer; PTEN; p53; mTOR; mLST8; REDD1; NOXA